What’s in a message : A systemic functional analysis of cancer prevention messages - Collin, Jerome; Ting, Su Hie (John Wiley & Sons Ltd, 2022)
This article provides some insights on how a particular reading from a theoretical framework can bring out details and problems with health communication posters. Using Michael Halliday’s Systemic Functional Linguistics (SFL) framework, the article examines cancer prevention messages in cancer posters produced by the Ministry of Health Malaysia.